Komunikasi Persuasif dalam Meningkatkan Minat Baca Gen Z di Dinas Perpustakaan Provinsi Sumatera Selatan - Sika Aprilia; Meisya Indriani; Iqbal Joneska; Abdur Razzaq; Muhamad Yudistira Nugraha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research discusses the role of persuasive communication in increasing Generation Z's interest in reading at the South Sumatra Provincial Library Service. Generation Z, which is highly influenced by technology and social media, shows a low tendency towards reading, preferring visual content over print media. The aim of this research is to determine persuasive communication in increasing the reading interest of generation z at the South Sumatra Provincial Library Service. The method used in this research is descriptive qualitative. In this research, researchers also used survey research, interviews and documentation to obtain data regarding persuasive communication in increasing Generation Z's interest in reading in the South Sumatra Province Library Service. The results of the research show that persuasive communication in increasing Generation Z's interest in reading is working quite well. Among them Persuasive communication activities carried out include mobile libraries, reading corners, banners. In conclusion, Persuasive Communication in increasing Generation Z' interest in reading at the South Sumatra Provincial Library Service has been going quite well. This can be seen from the increasing number of visitors and also the good response from visitors regarding the activities that have been carried out